Tenacificação de poli(ftalamida) (PPA) através de nanocompósitos com carbonato de cálcio e de blendas com copolímero estireno/etileno-butileno/estireno (SEBS) - Custódio, Gustavo José Saad (Universidade Federal de São Carlos, 2010)
This project aims the toughening of a high performance thermoplastic polyphthalamide (PPA). PPA resins is a good choice for special applications where the conditions are more severe than the ones an engineering thermoplastic can handle. In this study it was prepared two different types of PPA composites through the mixture of PPA and the elastomeric component and the nanoparticles of the mineral filler. The thermoplastic elastomer that was used is the block copolymer SEBS (styrene- ethylene/butylene-styrene), grafted with maleic anhydride and the mineral filler to be used is the nanosized calcium carbonate filler surface treated with stearic acid. The main emphasis of the study is to study the effects of incorporation of organic and inorganic additives in the toughening mechanisms, in the mechanical properties (especially impact strength) and in the structure of the PPA matrix and relationship between them. The mixture of the seventeen composition was done into a twin screw extruder. The inorganic nanoparticles of calcium carbonate did not alter significantly the properties of impact resistance, while the incorporation of SEBS obtained an increase up to ten times compared to pure PPA. However, the presence of rubber phase resulted in reduced stiffness of the system, which did not occurred in the nanocomposites, where such property has increased in value. Calcium carbonate in this system did not act as nucleating agent, and its incorporation decreased both the crystallization temperature as the degree of crystallinity. The presence of SEBS-g-MA in the blend PPA / SEBS promoted a decrease in particle size, which resulted in better mechanical properties.
Toughening of polyphthalamide (PPA) through nanocomposites of calcium carbonate and through styrene-ethylene/butylene-styrene block copolymer blends (SEBS)
Keywords: Polímeros; Tenacificação; Elastômero termoplástico; SEBS; PPA; ENGENHARIAS